Pulverized fuel ash solidification/stabilization of waste: comparison between beneficial reuse of contaminated marine mud and sediment - Y. Tang, Ivan; Y. S. Yan, Dickson; M. C. Lo, Irene; Liu, Tongzhou (Journal of Environmental Engineering and Landscape Management, 2015)
This study aimed to maximize the utilization of contaminated marine mud and sediment for beneficial reuse by solidification/stabilization (S/S) treatment with cement and pulverized fuel ash (PFA). For the purposes of waste maximization and enhancing the mechanical property of the S/S mixtures, mixing 75% by mass of either contaminated marine mud or sediment with 20% and 5% of cement and PFA, respectively, was found to be the optimal mix design. Their unconfined compressive strengths reached up to 8.32 MPa and 4.47 MPa, respectively. Apart from the mechanical property, according to the U.S.EPA, the TCLP results show that all regulated heavy metals were immobilized to a safe level and are available for engineering application such as fill material. The results of XRD reveal that the formation of CSH gel in the S/S treated mud and sediment is responsible for the strength development and heavy metal immobilization.